Antioxidant poteintial and activity of aerial parts of eight medicinal plants of Uttarakhand, India: Department of Biological Sciences, College of Basic Sciences & Humanities, Uttarakhand, India - Kashyap, Shakuli; Rao, PB; Mishra, P; Supriya, - (Bangladesh Journal of Botany, 2019)
The antioxidant potential of aerial parts of eight medicinal plant species were investigated by 1,1- diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, Ferrous ion-chelating (FCA) and ferric reducing antioxidant power assays in five different concentrations and the mean values ranged from 20.39 to 83.01%, 17.21 to 48.62% and 11.70 to 21.65 μg Trolox equivalent/mg extract, respectively. Total phenolic and flavonoid contents ranged from 4.83 to 10.46 μg, gallic acid equivalent/mg extract and 1.12 to 13.11 μg quercitin equivalent/mg extract. Enzymatic antioxidants (Unit/mg fresh weight): superoxide dismutase, catalase and peroxidase values ranged from 14.86 to 49.81, 60.00 to 141.33 and 0.25 to 0.60, respectively. Considering the overall assay M. Pudica can be considered as the potent candidate for displaying antioxidant activity among the experimental plants.